Monetary policy, housing, and collateral constraints - Thorsten Franz (Deutsche Bundesbank, 2019)
House-purchasing decisions and the possibility of existing homeowners to tap into their housing equity depend decisively on prevailing loan-to-value (LTV) ratios in mortgage markets with borrowing constrained households. Utilizing a smooth transition local projection (STLP) approach, I show that monetary policy shocks in the U.S. evoke stronger reactions in the housing sector in times of high LTV ratios, which, through changes in mortgage lending and mortgage equity withdrawals (MEWs), translate into larger effects of consumption. This result is more pronounced for contractionary shocks, in line with occasionally binding constraints. The strong procyclicality of LTV ratios reconciles these findings with past evidence on a less powerful transmission of monetary policy during recessions.
Keywords: E21; E52; G21; R31; 330; monetary policy; LTV ratio; mortgage equity withdrawals; collateral constraints; local projections; non-linear impulse responses